2017
DOI: 10.1002/2017ja024502
|View full text |Cite
|
Sign up to set email alerts
|

Validation of single spacecraft methods for collisionless shock velocity estimation

Abstract: The velocity of a collisionless shock (CS) is an important parameter in the determination of the spatial scales of the shock. The spatial scales of the shock determine the processes that guide the energy dissipation, which is related to the nature of the shock. During the pre‐ISEE era, estimations of relative shock‐spacecraft velocity (VSh) were based on spatial scales of the shock front regions, in particularly the foot. Multispacecraft missions allow more reliable identification of VSh. The main objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
5
5
0
Order By: Relevance
“…It is also in agreement with Giagkiozis et al. (2017), who measured a (3.4badbreak±1.4)0.3333emc/ωpe ramp for a Venusian shock. The clean monotonic jump we observed would fall under Newbury et al.…”
Section: Observations and Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It is also in agreement with Giagkiozis et al. (2017), who measured a (3.4badbreak±1.4)0.3333emc/ωpe ramp for a Venusian shock. The clean monotonic jump we observed would fall under Newbury et al.…”
Section: Observations and Resultssupporting
confidence: 92%
“…The observed ramp width agrees with Earth studies by Mazelle et al (2010), falling under their reported most probable values with ramp thicknesses below 5 c pe / , as well as several thin shocks reported by Hobara et al (2010) with ramps below 4 c pe / . It is also in agreement with Giagkiozis et al (2017), who measured a ( .…”
Section: 1029/2020ja028938supporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, when the B-field is switched off, only a smooth plasma expansion into the ambient (blue dashed line) can be seen. In the case when the magnetic field is applied, another clear signature of the magnetized shock, observed by satellite 27 , is the noticeable feature of a "foot" in the density profile, located in the shock upstream (US). It is due to the cyclic evolution of the plasma: the plasma in the foot is picked up to form the shock front, while the latter is also periodically dismantled by the Larmor.…”
mentioning
confidence: 99%
“…The piston front is steepened by the compression of the magnetic field (see also below). Besides, we can clearly see a "foot" structure ahead of the shock front in the upstream (US) region for the case with both ambient gas and B-field, indicating the formation of the magnetized shock 47 .…”
Section: B Density Characterization Through Optical Interferometrymentioning
confidence: 84%